The role of fruit heteromorphism in the naturalization of Asteraceae - Fenesi, Annamária; Sándor, Dorottya; Pyšek, Petr; Dawson, Wayne; Ruprecht, Eszter; Essl, Franz; Kreft, Holger; Pergl, Jan; Weigelt, Patrick; Winter, Marten; Van Kleunen, Mark (Annals of botany, 2019)
BACKGROUND AND AIMS: Fruit heteromorphism is considered to be a bet-hedging strategy to cope with spatially or temporally heterogeneous environments. The different behaviours of the fruit morphs of the same species might also be beneficial during naturalization, once the species has been introduced to a new range. Yet, no study to date has tested the association between fruit heteromorphism and global-scale naturalization success for a large set of plant species. METHODS: We compiled two large datasets on fruit heteromorphism in Asteraceae. One dataset was on native species in Central Europe (n = 321) and the other was on species frequently planted as ornamentals (n = 584). Using phylogenetic linear and logistic regressions, we tested whether heteromorphic species are more likely to naturalize outside their native range, and in more regions of the world than monomorphic species. We also tested whether the effect of heteromorphism is modulated by life history and height of the species. KEY RESULTS: We show that heteromorphic species were more likely to naturalize outside their native range. However, among the naturalized species, heteromorphic and monomorphic species did not differ in the number of world regions where they became naturalized. A short life span and tall stature both promoted naturalization success and, when life history and height were included in the models, the effect of fruit heteromorphism on the ability to naturalize became non-significant. Nevertheless, among tall plants, heteromorphic ornamental species were significantly more likely to become naturalized in general and in more regions than monomorphic species. CONCLUSIONS: Our results provide evidence that in Asteraceae the production of heteromorphic fruits is associated with naturalization success. It appears, however, that not fruit heteromorphism per se, but a successful combination of other biological traits in fruit heteromorphic species, namely short life span and tall stature, contributes to their naturalization success.
Keywords: monocarpy; Europe; Compositae; Alien species; dispersal; Evropa; naturalization; invasiveness; non-native species; Fruit; Asteraceae; ovoce; Phylogeny; zavlečené druhy; ekosystém; fruit heteromorphism; Ecosystem; seed heteromorphism; heterocarpy; fylogeneze; Introduced Species